Eradication of Mycoplasma Contaminations from Cell Cultures. Issue 1 (20th May 2014) - Uphoff, Cord C.; Drexler, Hans G.
Abstract: Mycoplasma contaminations have a multitude of effects on cultured cell lines that may influence the results of experiments or pollute bioactive substances isolated from the eukaryotic cells. The elimination of mycoplasma contaminations from cell cultures with antibiotics has been proven to be a practical alternative to discarding and re‐establishing important or irreplaceable cell lines. Different fluoroquinolones, tetracyclins, pleuromutilins, and macrolides shown to have strong anti‐mycoplasma properties are employed for the decontamination. These antibiotics are applied as single treatments, as combination treatment of two antibiotics in parallel or successively, or in combination with a surface‐active peptide to enhance the action of the antibiotic. The protocols in this unit allow eradication of mycoplasmas, prevention of the development of resistant mycoplasma strains, and potential cure of heavily contaminated and damaged cells. Consistent and permanent alterations to eukaryotic cells attributable to the treatment have not been demonstrated. Curr. Protoc. Mol. Biol . 106:28.5.1‐28.5.12. © 2014 by John Wiley & Sons, Inc.